Integrating Learning Techniques into iCAL4LA-Bijak Matematik Courseware to Motivate Low Achieving Children in Learning - Ahmad, Siti Zulaiha; Abdul Mutalib, Ariffin (Springer, Cham, 2017)
Children with learning difficulties require support during teaching and learning process. This study looks into the solution of learning difficulties confronted by the low achieving (LA) children who particularly have problems in literacy (reading) and numeracy (calculating). This study proposed the suitable learning techniques integrated into a learning course ware in order to ensure the children are engaged during the learning process as well as able to accomplish the whole learning content. The main objective is achieved through three research activities, which are (i) learning techniques selection, (ii) design and development of course ware, and (iii) user experience testing. As the result, this study initially found three learning techniques that are suitable for LA children.They are deployed into a course ware, iCAL4LA-Bijak Matematik in motivating the LA children to learn mathematics. The user experience testing revealed that it was motivating the LA children with percentage of mean, 97% as the ability in accomplishing overall sub-modules, as they can choose specific learning technique based on their preference.